Structural optimization of rib-to-crossbeam joint in orthotropic steel decks. (1st December 2021) - Fang, Heng; Iqbal, Nouman; Van Staen, Gilles; De Backer, Hans
Abstract: In orthotropic steel decks (OSDs), the rib-to-crossbeam joint is the most complex joint. When dealing with the intersection of the rib to the crossbeam, the prevailing approach is to design a cope hole in the crossbeam web. Nevertheless, the stress concentration induced by rib distortion makes this joint a fatigue-prone detail. Furthermore, the weld connecting the rib and the crossbeam heavily relies on the manual welding, which leads to high fabrication costs. In this paper, the possibility of canceling the cope hole is discussed. Calculation results of different modeling methods using solid elements and shell elements are first compared with experimental results. Then, several design parameters of an OSD without cope holes are investigated adopting the hot spot stress method. Based on the results of the parametric analyzes, optimized dimensions of the rib-to-crossbeam joint without cope holes are selected. The comparison of the models with and without cope holes is performed. Fatigue life assessments are conducted based on the influence surfaces of reference points predefined around the rib-to-crossbeam joint. Research results reveal that the most critical position for the rib-to-crossbeam joint without cope holes is at the curvature on the rib side. The radius of rib has a local influence on the points at the curvature. A larger radius could effectively lower the maximum stress range. The fatigue performance of the rib-to-crossbeam joint depends on the distribution of the tire load. Considering less fatigue-prone locations and reduced fabrication costs, the overall performance of the optimized rib-to-crossbeam joint without cope holes is better.